- #1

Shackleford

- 1,656

- 2

1) = 0

The denominator grows much faster than the numerator.

2) = 0

Each of these terms would simply be zero, right?

For 4) and 5), the f(x) = x

I simplified these to

4) = [(x-2)(x

5) = [(x-3)(x

http://i111.photobucket.com/albums/n149/camarolt4z28/Untitled2.png

http://i111.photobucket.com/albums/n149/camarolt4z28/Untitled.png

The denominator grows much faster than the numerator.

2) = 0

Each of these terms would simply be zero, right?

For 4) and 5), the f(x) = x

^{3}I simplified these to

4) = [(x-2)(x

^{2}+2x+4)]/(x-3)5) = [(x-3)(x

^{2}+3x+9)]/(x-2)http://i111.photobucket.com/albums/n149/camarolt4z28/Untitled2.png

http://i111.photobucket.com/albums/n149/camarolt4z28/Untitled.png

Last edited by a moderator: